Risk of refeeding syndrome, nutritional status, and dietitian involvement in treatment of hospitalized children and adolescents with eating disorders - Elva Björk Bjarnadóttir 1988- (2023)
Background and aims: Most guidelines recommend a dietitian in a multidiciplinary team in the treatment of inpatients with eating disorders. Studies from other countries have shown risk of refeeding syndrome, as well as vitamin and mineral deficiency in this group. The risk of refeeding syndrome and the nutritional status of hospitalized children and adolescents with eating disorders have not been assessed in Iceland and little is known about the involvement of dietitians in treatment of eating disorders internationally. The aim of the thesis was to evaluate the risk of refeeding syndrome in children and adolescents with eating disorders who were admitted to the child and adolescent psychiatric department of the national university hospital of Iceland (BUGL). Other aims include to assess the nutritional status and nutritional treatment during hospital stay, frequency of secondary diagnosis and the involvement of dietitians in the treatment. Design: Retrospective chart review. Methods: The study sample consist of children and adolescents, aged 6-18 years, admitted to the children’s psychiatric hospital in Iceland (BUGL) from January 1, 2010 to December 31, 2022 with the diagnosis of eating disorders. Information on age, gender, weight (at admission (+/-2 days) and at discharge (+/-2 days)), height and body mass index (BMI), other mental disorders diagnosis, length of hospital stay, number of previous and later hospital admissions and the number of hospital admission within the research period were all collected through hospital medical record. The ASPEN guidelines for pedeatrics patients were used when assessing risk for refeeding syndrome, which target i. weight (z- score), concentration of potassium, magnesium and phosphate and energy intake. Information on serum concentration of the following vitamins and minerals were also recorded: Cobalamin, folate, iron, ferritin and 25 hydroxy vitamin D. Results: Results are presented for 54 subjects admitted to the child and adolescents psychiatric department of the ...